Plup fiction: landscape simulation for participatory land use planning in Northern Lao PDR - Bourgoin, Jeremy; Castella, J.C. (2011)
A landscape simulation was designed and tested in Viengkham, a mountainous district in the north of Lao PDR. This social learning process was introduced by researchers affiliated with national research institutions to improve land use planning practices and increase the ownership of local people in the planning process. Twelve members of the village land management committees participated in the role play called “PLUP Fiction,” which is part of a stepwise process of participatory land use planning (PLUP). This article introduces the principles of land zoning, the sequence of events presented during the role play session, and the lessons learned from a series of experiments conducted in remote upland villages. The villagers gained an increased understanding of the issues at stake during a zoning process, thus demonstrating the relevance of this learning simulation tool. They were able to explore different zoning options, assess their respective advantages and constraints, and gradually improve their understanding of the consequences of land zoning on the environmental and economic values of the resulting landscape. The villagers also felt empowered by their newly acquired knowledge and well disposed toward negotiations to improve their current land use through more realistic plans. Long-term environmental concerns (ie biodiversity and carbon values) were fully integrated with shorter-term economic considerations in the collective decision-making process. Furthermore, “PLUP Fiction” has become a key tool for fully involving local communities in Reducing Emissions from Deforestation and Forest Degradation (REDD) through negotiations that are taking place during a land use planning process.